Income inequality ignored? An agenda for business and strategic organization. (August 2015) - Bapuji, Hari; Neville, Lukas
Despite a vibrant body of scholarship and a growing public discourse around the socio-political consequences of rising income inequality around much of the world, very little is known about the organizational consequences of societal-level income inequality. In this essay, we draw upon previous literature on the socio-political consequences of high income inequality to help identify its potential business consequences. In particular, we suggest that high levels of income inequality can give rise to (1) social movements that coerce and constrain firms' actions, (2) alternative organizational forms that displace existing organizations and (3) new political and regulatory risks that undermine firms' performance or survival. Using this argument, we emphasize the broader point that income inequality matters to firms and markets and that the study of inequality needs to be 'brought in from the cold' by organizational researchers. Furthermore, we outline a specific research agenda aimed at better understanding income inequality and how organizations can respond to it.